On shear resistance of almond skin reinforced PLA composite matrix-based scaffold using cancellous screw. Issue 2 (3rd April 2022) - Singh, Mohit; Kumar, Sudhir; Singh, Rupinder; Kumar, Ranvijay; Kumar, Vinay
ABSTRACT: The polylactic acid (PLA) matrix is being widely used as a scaffold for biomedical applications. But hitherto little has been reported on the use of 3D printed almond skin (AS) powder-reinforced matrix of PLA as a scaffold for ensuring shear resistance properties at different insertion angle, depth and infill pattern for holding a cancellous screw. This paper reports the shear fracture and morphological features of the 3D printed AS powder-reinforced matrix of PLA, prepared by fused deposition modelling for biomedical scaffolds using a cancellous pedicle screw. The study was performed using the angle of insertion 10°, 20° and 30°, depth of insertion of screw 40%, 70% and 100% in prototype and infill patterns (honeycomb, rectilinear and triangular) of 3D printed functional prototype. The study suggested that the maximum shear strength at peak (23.02 MPa) and maximum shear strength at break (22.90 MPa) were observed for honeycomb printing infill pattern, 100% insertion of screw and at 30° angle of insertion to prototype, whereas maximum modulus of toughness was observed for rectilinear pattern with 100% insertion of screw and 20° angle of insertion. Further morphological study was performed on the fractured surface to support the mechanical results obtained by pull-out test for ensuring shear resistance. Overall the study will be useful for an orthopaedic surgeon for ensuring angle, depth of insertion and infill pattern selection for minimising the shear fracture of the scaffold.